New practice readers :Book F /Donald G. Anderson. - Anderson, Donald George,1913-
Books B, F, and G by D. G. Anderson; Books C, D, and E by C. R. Stone, with L. Barton (Book C), A. Eliasberg (Book D), and E. Dolan (Book E).